Enhancing Digital Literacy and 4Cs Skills through Project-Based Deep Learning in Kurikulum Merdeka - Budi Tri Cahyono; Relly Prihatin; Taufiq Subhanul Qodr; Mochamad Kamil Budiarto (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examines the implementation of Deep Learning within the Merdeka Curriculum as a response to educational transformation in the digital age, which demands 21st-century competencies, namely critical thinking, creativity, collaboration, communication, digital literacy, and Pancasila-based character among elementary students. The study aims to evaluate the effectiveness of a project-based approach in integrating technological skills while strengthening national identity. A mixed-method design was employed, combining phenomenology and a one-group pretest-posttest model involving teachers, principals, and fifth-grade students from SD Negeri Sondakan and SD Negeri Tegalrejo in Surakarta. Data were gathered through in-depth interviews, observation, documentation, pretests, and posttests, then analyzed using triangulation, descriptive statistics, and ANOVA. The findings indicate improved students’ technology mastery, with success rates of 93.33% in Sondakan and 84.62% in Tegalrejo. Supporting factors included school leadership, teacher collaboration, and parental involvement. These results show that Deep Learning effectively strengthens digital literacy, the 4Cs, and students’ national character in diverse elementary school contexts.